2013
DOI: 10.1590/s1984-82502013000700004
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of water-soluble phosphorhydrazone dendrimers

Abstract: 1984-8250Dendrimers are hyperbranched and perfectly defined macromolecules, constituted of branches emanating from a central core in an iterative fashion. Phosphorhydrazone dendrimers constitute a special family of dendrimers, possessing one phosphorus atom at each branching point. The internal structure of these dendrimers is hydrophobic, but hydrophilic terminal groups can induce the solubility of the whole structure in water. Indeed, the properties of these compounds are mainly driven by the type of termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…There are three ways to conjugate PS in dendrimers: (i) PS is trapped in the voids of a dendrimer; (ii) PS is covalently bound to the dendrimer; (iii) PS is used as a scaffold to form a dendrimer [114].…”
Section: Nanotechnology-based Drug Delivery Systemsmentioning
confidence: 99%
“…There are three ways to conjugate PS in dendrimers: (i) PS is trapped in the voids of a dendrimer; (ii) PS is covalently bound to the dendrimer; (iii) PS is used as a scaffold to form a dendrimer [114].…”
Section: Nanotechnology-based Drug Delivery Systemsmentioning
confidence: 99%
“…For our next scaffold, harboring six propargylated functionalities, we choose the previously described hexachlorocyclotriphosphazene core 14 (N 3 P 3 Cl 6 ) [ 28 , 33 , 34 , 35 ]. The choice for this dense hexavalent core was based on previous observations by the Majoral’s group who showed that it was biologically favorable over several other scaffolds and that it can readily form dendrimers of very high generation [ 36 , 37 , 38 , 39 , 40 ]. Toward this goal, diol 12 was monopropargylated (propargyl bromide, K 2 CO 3 , acetone, r.t., 12 h) to afford 13 (43%) ( Scheme 3 ) which was treated with 14 under basic conditions (Cs 2 CO 3 , THF, 70 °C, 17 h) to provide 15 in essentially quantitative yield (98%).…”
Section: Resultsmentioning
confidence: 99%
“…Ability to control its size, number of functional groups available for modifications and predictability of the amount of incorporated drug makes them ideal DDS with reproducible pharmacokinetics (62,203). PS can be trapped in the voids of a dendrimer, covalently bound to the dendrimer (204) or used as a scaffold to form a dendrimer (205). They can be conjugated with tumor-targeting peptides as well (204).…”
Section: Formulations and Dds Of Pcs And Mpcsmentioning
confidence: 99%